2013
DOI: 10.1007/s10916-013-9960-5
|View full text |Cite
|
Sign up to set email alerts
|

Benefits and Challenges of Electronic Health Record System on Stakeholders: A Qualitative Study of Outpatient Physicians

Abstract: Electronic health record system (EHRS) is an important healthcare innovation associated with many controversies about the benefits and challenges to different stakeholders. The aim of this study was to investigate the utility of EHRS by outpatient physicians in Macao and to identify, in their opinions, the significance of EHRS on health institutes, patients, and physicians. Semi-structured interviews were conducted with 32 physicians who worked in the outpatient department. The interview data showed that 78% p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
48
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(48 citation statements)
references
References 24 publications
0
48
0
Order By: Relevance
“…The information patients share with their physicians is so sensitive that patients have expressed the desire to remove some of their information from the system [72] and physicians are more reluctant to use the system because of legal concerns and doctor-patient confidentiality [75]. These issues are crucial in the design and adoption of the system, and an EHR must protect both patients' medical records and physicians' integrity.…”
Section: Discussion Conclusion and Policy Implicationsmentioning
confidence: 99%
See 1 more Smart Citation
“…The information patients share with their physicians is so sensitive that patients have expressed the desire to remove some of their information from the system [72] and physicians are more reluctant to use the system because of legal concerns and doctor-patient confidentiality [75]. These issues are crucial in the design and adoption of the system, and an EHR must protect both patients' medical records and physicians' integrity.…”
Section: Discussion Conclusion and Policy Implicationsmentioning
confidence: 99%
“…From the physicians' perspective, concerns regarding privacy and confidentiality were found to hinder physicians' acceptance and adoption of EHR [75], thus showing how these issues can impact EHR use that extends beyond patients' reservations.…”
Section: Legal Issues Concerning Ehr and Hiementioning
confidence: 99%
“…Personal health records (PHRs) have the potential to substantially improve communication in healthcare such that authorized stakeholders have immediate access to patient health data in real time (White and Danis 2013). This would significantly reduce misunderstandings, redundant examinations, adverse drug events and delays in treatment (Chao et al 2013). In addition, the transparent access to personal health data might increase health awareness of the patient (Meier et al 2019).…”
Section: Introductionmentioning
confidence: 99%
“…However, Deutsch et al (2010); Greenhalgh et al (2009); Lorenzi et al (2009); Madore et al (2015); and Smith (2003) have argued that EHRS implementation is very complicated due to the shortage of experience with its implementation and the associated issues. Although, the barriers to EHRS implementation have been described, many of them remain unresolved (Chao et al, 2013). Therefore, it has been suggested that further research and investigation is necessary to overcome these barriers (Chao et al, 2013).…”
Section: Project Championsmentioning
confidence: 99%
“…Although, the barriers to EHRS implementation have been described, many of them remain unresolved (Chao et al, 2013). Therefore, it has been suggested that further research and investigation is necessary to overcome these barriers (Chao et al, 2013).…”
Section: Project Championsmentioning
confidence: 99%